Therapeutic Manuka Honey: No Longer So Alternative - Carter, Dee A.; Blair, Shona E.; Cokcetin, Nural N.; Bouzo, Daniel; Brooks, Peter; Schothauer, Ralf; Harry, Elizabeth J. (Frontiers in Microbiology, 2016)
Medicinal honey research is undergoing a substantial renaissance. From a folklore remedy largely dismissed by mainstream medicine as “alternative”, we now see increased interest by scientists, clinical practitioners and the general public in the therapeutic uses of honey. There are a number of drivers of this interest: first, the rise in antibiotic resistance by many bacterial pathogens has prompted interest in developing and using novel antibacterials; second, an increasing number of reliable studies and case reports have demonstrated that certain honeys are very effective wound treatments; third, therapeutic honey commands a premium price, and the honey industry is actively promoting studies that will allow it to capitalize on this; and finally, the very complex and rather unpredictable nature of honey provides an attractive challenge for laboratory scientists. In this paper we review manuka honey research, from observational studies on its antimicrobial effects through to current experimental and mechanistic work that aims to take honey into mainstream medicine. We outline current gaps and remaining controversies in our knowledge of how honey acts, and suggest new studies that could make honey a no longer “alternative” alternative.